VAN GOGH IMMERSIVE EXHIBITION: LESSONS & OPPORTUNITIES FOR TRADITIONAL CULTURAL EXPRESSIONS DEVELOPMENT IN INDONESIA - Mayana, Ranti Fauza; Santika, Tisni (Transnational Business Law Journal, 2023)
Van Gogh's immersive exhibition is held in more than 90 cities around the world including Berlin, Beijing, Paris, London, Madrid, Rome, Sydney, and Jakarta. Until mid-2023, the exhibition has been attended by more than 8.5 million visitors and is an example of intellectual property development. Corresponding to business, IP Development is the capitalization of ideas, creativity, and innovation in producing products or services that contain creative content through systems of human activity related to the creation, production, distribution, and consumption of goods and services that have cultural, artistic, aesthetic, intellectual and emotional values for consumers. This paper employs a descriptive-analytical approach to describe the relevant legal rules and legal theories of copyright and their application in the IP development of artworks for businesses and the opportunities for Indonesia. The finding of the study indicates that immersive technology as a platform for the development of artworks based on Traditional Cultural Expressions (TCEs) potentially creates opportunities for intellectual property legal protection and business development of Indonesia’s TCEs in the frame of Cultural Industries. The commercialization of TCEs using immersive technologies potentially helps in fulfilling two key objectives: capturing new audiences and contributing to economic profit. However, the involvement of legal and non-legal elements as the basis for the implementation conducted in a collaborative framework between state holders and relevant stakeholders is required